Caracterização petrográfica da alteração hidrotermal do minério de cobre e ouro do Alvo Suruca SW, Alto Horizonte (GO) - Pian, Tais Bischof [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The Chapada magmatic-hydrothermal deposit represents one of the main copper and gold mines of the Goiás Magmatic Arc, located in the northern part of the state of Goiás. In this context, Suruca SW target is located northeast of Chapada Mine and hosts copper mineralizations and gold on the metavolcanic - sedimentary sequence of Mara Rosa. Studies in literature, in relation to host rock, hydrothermal alteration and target mineralization styles are scarce. Thus, this work has as main objective the characterization of the hydrothermal alteration of the Suruca SW target, such as the petrographic description of the host rock and the types and styles of the mineralization, besides relating the best Cu and Au contents with the lithologies and changes described. Thus, 6 types of hydrothermal alterations were defined for the target, temporally represented by: biotitization, muscovitization, epidotization, propylitic alteration, muscovitization 2 and silicification, the first 5 in a pervasive style and the last in a confined style. The host rocks of the mineralizations are metavulcanic intermediary and metaquartz porphyritic diorites. The mineralization takes place in two styles: pervasive, associated to epidotization and propytitic alteration, subordinately, associated to biotitization and muscovitization; and confined to quartz venules, associated with silicification, which denotes the deposit the best ranges of contents. The main ore minerals are chalcopyrite and, secondarily, pyrite. Gold, on the other hand, is closely related to the sulfides (chalcopyrite and pyrite), which occurs even in the interstices or at its edges, and also interstitial to quartz crystals, but still adjacent to the crystals of sulphides. Geochemical data allow to correlate and evidence the strong relationship of auriferous mineralizations with copper in the target. Finally, there are several discussions about the genetic model about the Suruca SW target, which includes...

O depósito magmático-hidrotermal de Chapada representa uma das principais minas de cobre e ouro do Arco magmático de Goiás, localizada no norte do estado de Goiás. Nesse contexto, o Alvo Suruca SW localiza-se a nordeste da Mina Chapada e hospeda mineralizações de Cu e Au em rochas da sequência metavulcano sedimentar Mara Rosa. Trabalhos na literatura para o Alvo são escassos, dessa forma, esse trabalho tem como objetivo principal a caracterização da alteração hidrotermal do Alvo Suruca SW, tais como a descrição petrográfica da rocha hospedeira e dos tipos e estilos da mineralização, além de relacionar os teores de Cu e Au com as litologias e alterações descritas. Com isso, definiu-se 6 tipos de alterações hidrotermais para o Alvo, temporalmente representadas por: biotitização, muscovitização, epidotização, alteração propilítica, muscovitização 2 e silicificação, sendo as 5 primeiras em estilo pervasivo e a última em estilo confinado. As rochas hospedeiras das mineralizações são metavulcânicas intermediárias e metaquartzo-diorito porfiritico. A mineralização ocorre em dois estilos: disseminada, associada a epidotização e alteração propilítica, subordinadamente, associada a biotitização e muscovitização; e confinada a vênulas de quartzo, associada a silicificação, essa que denota ao depósito os melhores intervalos de teores. Como principais minerais de minério têm-se a calcopirita e, secundariamente, a pirita. Já o ouro está intimamente ligado aos sulfetos (calcopirita e pirita), na qual ocorre incluso, nos interstícios ou nas suas bordas, e também ocorre intersticial a cristais de quartzo, mas ainda adjacentes aos cristais de sulfetos. Dados geoquímicos permitem correlacionar e evidenciar a forte relação das mineralizações auríferas com as cupríferas no Alvo. Por fim, são diversas as discussões a respeito do modelo genético acerca do alvo Suruca SW, em que engloba sistemas do...
Keywords: Mineralogia; Petrologia; Alteração hidrotermal; Cobre - Minas e mineração; Ouro - Minas e mineração; Geoquímica; Geologia estrutural; Goias (Estado)